ЕКОНОМІЧНА СУТНІСТЬ ТА ВИДИ ФІНАНСОВИХ ПОСЛУГ - Дубина, Максим Вікторович (Науковий журнал «Світ фінансів», 2017)
Дубина М. В. Економічна сутність та види фінансових послуг. Досліджено сутність поняття “фінансова послуга”. Проведено івент-аналіз наявних у літературі трактувань визначення сутності зазначеного поняття, що дало можливість з’ясувати два наукові підходи: результативний і процесний. Теоретичний базис дослідження таких послуг поглиблений візуалізацією та описом концептуальної моделі фінансової послуги, ідентифікацією її ознак та класифікацією видів окреслених послуг. Дубина М. В. Экономическая сущность и виды финансовых услуг. Исследована сущность понятия “финансовая услуга”. Проведен ивент-анализ имеющихся в литературе трактовок сущности указанного понятия, что позволило выяснить два научных подхода: результативный и процессный. Теоретический базис исследования таких услуг углублен визуализацией и описанием концептуальной модели финансовой услуги, идентификацией ее признаков и классификацией видов таких услуг. Dubyna M. Economic essence and types of financial services. Introduction. The financial services market is an important component of the national economy. Exactly through the mechanisms for providing the financial services within the entire system of the national economy the movement of financial resources in the modern realities is realized. This makes possible to create the conditions for the efficient provision of the defined services and increases the need for research in studying the details of the financial services, deepening the theoretical principles of their functioning.Purpose. The aim of the article is to study the essence of the category “a financial service”, to investigate the peculiarities of providing such services.Results. Within the article the attempt was made to investigate essence of the economic category “a financial service”. For these purposes the inductive method of knowledge was used, and essence of such categories as “finances” and “service” was defined. Also, the event-anal-ysis of the existing in the literature interpretations of the definition “the financial services” was conducted and they were systematized . That allowed to identify two scientific approaches to its identification: resultative and process ones, their essence and differences was described. To deepen the theoretical basis of the study of the financial services the main peculiarities of the financial service were analysed, the attempt to classify the types of the financial services was made in the article.Conclusion. As a result the financial service was proposed to be considered as an inmaterial form of the result of the interaction, which has consumer value, between the agents in the process of satisfying one of them (by the producer of the financial services), the financial needs of others (of the consumer of the financial services or the client) on the basic of their own account, account of the clients or from borrowed funds of the other customers in accordance with applicable law with the purpose to get profit, to preserve the value of assets or to achieve social effect from the realization of such services.